AN EFFECTIVE MECHANISM OF SEISMIC SIGNAL GENERATION DURING THE INTERACTION OF TORNADOES WITH THE EARTH'S SURFACE - Ingel L.Kh. (My University, 2004)
The possibilities of generating of seismic waves of notable intensity related to tornadoes have been considered in several recent publications. In principle, seismic signals can be used for remote registration of tornadoes, and the realization of this idea could widen the possibilities of forecasting these hazardous phenomena. Information about the registration of such events and discussion of possible mechanisms of their generation are given in [1–5]. Preliminary estimates indicate that some of the suggested mechanisms can, in principle, provide a signal intensity powerful enough for their remote recording by modern seismic equipment (however, the issue of discriminating signals from remote tornadoes against the background of noise related, in particular, to signals from atmospheric processes occurring closer to the seismic station is very pressing). It is more difficult to explain soil vibrations that have such an amplitude that they can allegedly be detected at a distance of one or even a few kilometers from a tornado [2, 3]. In our work, we consider the generation mechanism of previously ignored seismic signals, namely, pressure fluctuations in a tornado related to cyclostrophic adjustment of pressure and velocity fields. Estimates indicate that this mechanism can be significantly more effective in a certain range of frequencies than those discussed before.